1989
DOI: 10.1007/bf00015554
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a C3 plant Rubisco SSU gene in regenerated C4 Flaveria plants

Abstract: We report the successful transformation, via Agrobacterium tumefaciens infection, and regeneration of two species of the genus Flaveria: F. brownii and F. palmeri. We document the expression of a C3 plant gene, an abundantly expressed ribulose 1,5-bisphosphate carboxylase/oxygenase small subunit gene isolated from petunia, in these C4 plants. The organ-specific expression of this petunia gene in Flaveria brownii is qualitatively identical to its endogenous pattern of expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Martineau et aL (1989) reported the transformation of two C4-1ike Flaveria species using Agrobactedum infection of mature leaf explants followed by regeneration of transformed shoots from callus. Shoots were regenerated on Murashige and Skoog medium containing 4 mg 1-1 6-(7-~,-dimethylallylamino)purine (2iP) and 1 mg 1-1 indole acetic acid (IAA).…”
Section: Development Of a Shoot Regeneration Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Martineau et aL (1989) reported the transformation of two C4-1ike Flaveria species using Agrobactedum infection of mature leaf explants followed by regeneration of transformed shoots from callus. Shoots were regenerated on Murashige and Skoog medium containing 4 mg 1-1 6-(7-~,-dimethylallylamino)purine (2iP) and 1 mg 1-1 indole acetic acid (IAA).…”
Section: Development Of a Shoot Regeneration Methodsmentioning
confidence: 99%
“…The ability to compare closely related species with different physiological properties and different programmes of gene regulation should be a helpful experimental approach. Martineau et al (1989) reported the transformation of two C4-1ike intermediate species, Flaveria palmeri and F. brownii, suggesting that C4 Flaveria species might be good candidates for transformation. F. bidentis is a fully C4 species with a wide geographic distribution, probably native to South America (Powell, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…C4 genes have been introduced into C3 plants and vice versa with mixed success. A petunia (C3) rbcS gene was transcrip tionally active when introduced into F. brownii (C4-like), although cell localization was not described (91). The maize C4 ppc, ppdk and rbcS promoters drive transcription of a GUS reporter gene in leaf mesophyll and other photosynthetic cells of transgenic tobacco (99).…”
Section: Regulation Of Individual C4 Genesmentioning
confidence: 99%
“…In contrast, dicot but not monocot rbcS promoters are expressed in C3 dicot cells (Keith and Chua, 1986; this study). In a C4 dicot plant flaveria, a C3 dicot rbcS promoter (petunia) is active after transformation (Martineau et al, 1989). The upstream silencers of maize rbcS revealed in protoplast transient expression might be important for mesophyll-specific repression.…”
Section: Maize Rbcs Expression In Mesophyll Cells 1s a Default Mechanmentioning
confidence: 99%